REVIEW OF THE BOOK “HISTORY OF PSYCHOLOGY” WRITTEN BY ASSOC. PROF. STOIL MAVRODIEV, D.SC - Nikolova, Simona Vasileva (Psychological thought, 2025)
The review of the book "History of Psychology" presents a comprehensive theoretical and historical study conducted by Stoil Mavrodiev, dedicated to the evolution of psychological thought from antiquity to contemporary trends. The book is structured chronologically and thematically, emphasizing key schools, personalities, and paradigms in psychology. The author highlights the connection between historical roots and current challenges, including neuroscience, artificial intelligence, applied psychology, and global crises such as pandemics and climate change. This second expanded edition enriches the previous one from 2015 with new sections on existential psychology, classical experiments, the development of Russian and Bulgarian psychological traditions, as well as contemporary perspectives like the impact of digital technologies on mental health. The book is a valuable resource for students, researchers, and professionals, offering in-depth analysis, interdisciplinary connections, and perspectives on the future of science, with an emphasis on the role of psychology in addressing global challenges.